PERANAN KEPALA SEKOLAH PAUD SEBAGAI MANAJER DI LINGKUNGAN UPTD KECAMATAN TAMPAN KOTA PEKANBARU - Apriani, Rike; Indarto, Wusono; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is: to determine the role of PAUD headmaster as managers in UPTD district Tampan city of Pekanbaru. So it can be formulated problem of this research is: How role of principal of PAUD as manager in environment UPTD district Tampan city of Pekanbaru? Theoretically, this research is useful to give thought contribution to scholarship related to the role of PAUD headmaster as manager in UPTD environment, Tampan sub-district, Pekanbaru city. This research was conducted in PAUD Sekecamatan Tampan Pekanbaru. The time of this research was conducted in June to September 2016. This research was conducted at PAUD Sekecamatan Tampan Pekanbaru. This research is conducted in June to September 2016. This research type is descriptive research that is research which try to tell problem solving that exist now based on data, and also present data, analyze and interpret. Measurements of PAUD headmaster role as manager in UPT district environment Tampan city Pekanbaru using questionnaire as many as 34 duplicate, highest score for each statement is 5 and lowest score is 1 which is disseminated to 34 subject of research. Based on the result of the research, it can be concluded that the role of PAUD headmaster as manager in UPTD environment of Tampan city of Pekanbaru is very good because it has an average of 81,07%. That is, the principal of PAUD has been acting as manager in UPT district district Tampan city Pekanbaru very well.Keyword: The Role Of PAUD Headmaster